PENGARUH MODEL PEMBELAJARAN SAINS TEKNOLOGI MASYARAKAT (STM) TERHADAP SIKAP PEDULI LINGKUNGAN DAN HASIL BELAJAR SISWA PADA MATERI PENCEMARAN LINGKUNGAN KELAS VII SMP/MTS - Hosnia, Hosnia; Laila Khusnah (Indonesian Journal of Science Learning (IJSL), 2024)
The low attitude of caring for the environment and student learning outcomes often occurs in the world of education. These problems can be related to the applied learning model. The purpose of this study was to find out whether there is an influence of the Science Technology Society (STM) learning model on environmental care attitudes and student learning outcomes on environmental pollution material for class VII SMP/MTs. This research uses quantitative research, this type of experimental research with quasi experimental design in the form of nonequivalent group posttest only design. The population of this study was students of class VII SMPN 1 Rambipuji, using the purposive sampling technique, namely class VII A as the control class and VII B as the experimental class. Data collection technique using tests, questionnaires, and documentation. Data analysis technique using descriptive statistics and inferential statistics with the Z test. The result showed that there was a significant influence of the Science Technology Society (STM) learning model on environmental care attitudes and student learning outcomes on environmental pollution material for class VII SMP/MTs with a significant value of 0,000; and there is a significant influence of the Science Technology Society (STM) learning model on learning outcomes with a significant value of 0,000.